Cryptography: A study on the legal position of symmetric and asymmetric encryption under the Malaysian digital signature act 1997 - Nazli, Ismail@Nawang; Aminuddin, MUstaffa; Mohd Lotpi, Mohd Yusob (2015)
Electronic commerce involves the exchange of goods and services for some form of money in the virtual world without the involvement of face-to-face communication. For that reason, the security of electronic payment system is very crucial for the success and widespread acceptance of such online transactions. Over the past few years, technological developments have made significant contributions to secure the electronic payment system from theft and manipulation by interlopers and eavesdroppers. One way to have secure transmissions of the transaction information between the contracting parties is the adoption of cryptography. Cryptography refers to the art and science of keeping information secret by using a code or cipher. It can be an effective tool for the secure use of information and communication technology by ensuring confidentiality, integrity and availability of data and by providing authentication and non-repudiation mechanisms for that data. And this technology has been primarily employed by providers of electronic and digital signatures in online transactions. Due to the importance of cryptography, it is therefore pertinent in this study to explore in details the technical aspects of cryptography and its classification into symmetric (secret key) cryptography and asymmetric (public key) encryption. The study will then examine the legal position of symmetric and asymmetric encryption under the Digital Signature Act 1997 (the DSA) and highlight any loopholes or lacunae in the DSA.